The secret chapter : an invisible library novel - Cogman, Genevieve (Cogman, Genevieve. Invisible library novel., 2020)
"In the latest novel in Genevieve Cogman's historical fantasy series, Irene and Kai have to team up with an unlikely band of misfits to pull off an amazing art heist--or risk the wrath of the dangerous villain with a secret island lair. A Librarian's work is never done, and once Irene has a quick rest after their latest adventure, she is summoned to the Library. The world where she grew up is in danger of veering deep into chaos, and she needs to obtain a particular book to stop this from happening. No copies of the book are available in the Library, so her only choice is to contact a mysterious Fae information broker and trader of rare objects: Mr. Nemo. Irene and Kai make their way to Mr. Nemo's remote Caribbean island and are invited to dinner, which includes unlikely company. Mr. Nemo has an offer for everyone there: he wants them to steal a specific painting from a specific world. He swears that he will give each of them an item from his collection if they bring him the painting within the week. Everyone takes the deal. But to get their reward, they will have to form a team, including a dragon techie, a Fae thief, a gambler, a driver, and the muscle. Their goal? The Kunsthistorisches Museum in Vienna, in a early twenty-first century world, where their toughest challenge might be each other"--